Negligible-Cost and Weekend-Free Chemically Defined Human iPSC Culture - Kuo, Hui-Hsuan (Stem Cell Reports, 2020)
Human induced pluripotent stem cell (hiPSC) culture has become routine, yet the cost of pluripotent cell media, frequent medium changes, and the reproducibility of differentiation have remained restrictive. Here, we describe the formulation of a hiPSC culture medium (B8) as a result of the exhaustive optimization of medium constituents and concentrations, establishing the necessity and relative contributions of each component to the pluripotent state and cell proliferation. The reagents in B8 represent only 3% of the costs of commercial media, made possible primarily by the in-lab generation of three E. coli-expressed, codon-optimized recombinant proteins: fibroblast growth factor 2, transforming growth factor β3, and neuregulin 1. We demonstrate the derivation and culture of 34 hiPSC lines in B8 as well as the maintenance of pluripotency long term (over 100 passages). This formula also allows a weekend-free feeding schedule without sacrificing capacity for differentiation.